KMT2A‐D pathogenicity, prevalence, and variation according to a population database. (8th December 2022) - Larson, Jenna K.; Hunter‐Schlichting, DeVon N.; Crowgey, Erin L.; Mills, Lauren J.; Druley, Todd E.; Marcotte, Erin L.
Abstract: Introduction: The KMT2 family of genes is essential epigenetic regulators promoting gene expression. The gene family contains three subgroups, each with two paralogues: KMT2A and KMT2B; KMT2C and KMT2D; KMT2F and KMT2G. KMT2A‐D are among the most frequent somatically altered genes in several different cancer types. Somatic KMT2A rearrangements are well‐characterized in infant leukemia (IL), and growing evidence supports the role of additional family members ( KMT2B, KMT2C, and KMT2D ) in leukemogenesis. Enrichment of rare heterozygous frameshift variants in KMT2A and C has been reported in acute myeloid leukemia (AML), IL, and solid tumors. Currently, the non‐synonymous variation, prevalence, and penetrance of these four genes are unknown. Methods: This study determined the prevalence of pathogenic/likely pathogenic (P/LP) germline KMT2A‐D variants in a cancer‐free adult population from the Genome Aggregation Database (gnomAD). Two methods of variant interpretation were utilized: a manual genomic variant interpretation and an automated ACMG pipeline. Results: The ACMG pipeline identified considerably fewer P/LP variants ( n  = 89) compared to the manual method ( n  = 660) in all 4 genes. Consequently, the total P/LP prevalence and allele frequency (AF) were higher in the manual method (1:112, AF = 4.46E‐03) than in ACMG (1:832, AF = 6.01E‐04). Multiple ancestry‐exclusive P/LP variants were identified along with an increased frequency in males compared to females. Many of these variants identified in this population database are also associated with severe juvenile conditions. Conclusion: These data demonstrate that putatively functional germline variation in these developmentally important genes is more common than previously appreciated and identification in cancer‐free adults may indicate incomplete penetrance for many of these variants. Future research should examine a genetic predisposing role in IL and other pediatric cancers. Abstract : This analysis highlights the pathogenic spectrum of heterozygous KMT2A, KMT2B, KMT2C, and KMT2D mutation found in the gnomAd database, utilizing the non‐cancer adult cohort. Pathogenic mutations associated with severe pediatric cancer and genetic syndromes were identified in an ostensibly healthy adult. This analysis provides insight into the prevalence and penetrance of these pathogenic mutations in the general population.